If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2v+2)+3v=6(v-5)+2v
We move all terms to the left:
6(2v+2)+3v-(6(v-5)+2v)=0
We add all the numbers together, and all the variables
3v+6(2v+2)-(6(v-5)+2v)=0
We multiply parentheses
3v+12v-(6(v-5)+2v)+12=0
We calculate terms in parentheses: -(6(v-5)+2v), so:We add all the numbers together, and all the variables
6(v-5)+2v
We add all the numbers together, and all the variables
2v+6(v-5)
We multiply parentheses
2v+6v-30
We add all the numbers together, and all the variables
8v-30
Back to the equation:
-(8v-30)
15v-(8v-30)+12=0
We get rid of parentheses
15v-8v+30+12=0
We add all the numbers together, and all the variables
7v+42=0
We move all terms containing v to the left, all other terms to the right
7v=-42
v=-42/7
v=-6
| 10x^2+8+24=0 | | 6.5-4x-20=-6x+48 | | .5x-3.69=x-1.9-2.39 | | 11x-9=7x-5 | | 4p-5(p+1)=14 | | 40+6p=5(1-7p)-6 | | 6x+4=4x+38 | | 80/2(400)=4/2x | | 6(w+4)=76+2w | | 1-x+5x=17 | | y=3.5^2 | | 9c=75+0.5c | | 5u+7u-8=4u-18-6 | | y=12.25 | | 6a+2a+23=6+3a+7 | | 10+n/3=7 | | 5u+7u-8=4u-18-8 | | 2y^2-20y+37,5=0 | | -3x-8=17-4x | | -12(k+)=60 | | 2x-16=4x+18 | | 4m+2=6m-10 | | 6x+19=100 | | 3m×m=102 | | .5(m+4=3(m-1) | | 8x-3(2x-4)=4(3×-6)-4x | | 8x+4-2x=-6x-14+x | | -p+3=12 | | 6s−4=8(2+1/4(s)) | | 8=5=5p | | -7x+1+5x=11 | | −6=3x |